PROSES BERPIKIR MAHASISWA DITINJAU DARI KEMAMPUAN METAKOGNISI MAHASISWA DALAM MENDESAIN PEMBELAJARAN MATEMATIKA - Theresia, Olivia (Universitas Negeri Surabaya, 2019)
Metacognition is an important concept in cognition theory, which can be interpreted simply as an attempt at what is thought. The purpose of this study was to determine the students thinking process in term of students metacognition skills in designing mathematics learning. The research subjects were 6 undergraduate students of mathematics education at Sanata Dharma University. The object of research is the learning process carried out by students. This type of research is descriptive qualitative research because data retrieval is obtained through projects and interviews then data is presented in the form of sentence descriptions. Research results show that students who have good metacognition skills tend to be able to design complete learning through directing awareness and regulating their thinking processes. Students who have poor metacognition skills tent to believe in the thinking process so that is does not carry out the process of metacognition on the steps to design mathematical learning. Through the design of learning students can be trained to direct their metacognition abilities. This metacognition ability cannot always be seen in the problem solving process.